Does Rabbit Antithymocyte Globulin (Thymoglobuline®) Have a Role in Avoiding Delayed Graft Function in the Modern Era of Kidney Transplantation? - Lluís Guirado (Journal of Transplantation)
Delayed graft function (DGF) increases the risk of graft loss by up to 40%, and recent developments in kidney donation have increased the risk of its occurrence. Lowering the risk of DGF, however, is challenging due to a complicated etiology in which ischemia-reperfusion injury (IRI) leads to acute tubular necrosis. Among various strategies explored, the choice of induction therapy is one consideration. Rabbit antithymocyte globulin (rATG [Thymoglobuline]) has complex immunomodulatory effects that are relevant to DGF. In addition to a rapid and profound T-cell depletion, rATG inhibits leukocyte migration and adhesion. Experimental studies of rATG have demonstrated attenuated IRI-related tissue damage in reperfused tissues, consistent with histological evidence from transplant recipients. Starting rATG intraoperatively instead of postoperatively can improve kidney graft function and reduce the incidence of DGF. rATG is effective in preventing acute rejection in kidney transplant recipients at high immunological risk, supporting delayed calcineurin inhibitor (CNI) introduction which protects the graft from early insults. A reduced rate of DGF has been reported with rATG (started intraoperatively) and delayed CNI therapy compared to IL-2RA induction with immediate CNI in patients at high immunological risk, but not in lower-risk patients. Overall, induction with rATG induction is the preferred choice for supporting delayed introduction of CNI therapy to avoid DGF in high-risk patients but shows no benefit versus IL-2RA in lower-risk individuals. Evidence is growing that intraoperative rATG ameliorates IRI, and it seems reasonable to routinely start rATG before reperfusion.